Local Government Policy in The Spatial Planning of Autonomous Regions: Between Development Interests and Environmental Sustainability - Otom Mustomi; Endang Sutrisno; Untoro Untoro; Ratna Galuh Manika Trisista; Abdul Haris (AMCA, 2026)
Regional spatial planning is important in achieving sustainable development in autonomous regions. However, in its implementation, spatial planning policies often contradict the public interest, economic growth, and efforts to preserve the environment. It aims to evaluate how local governments manage spatial planning within the framework of regional autonomy and assess the extent to which the policies implemented can create a balance between regional growth and environmental protection. The research method uses the qualitative approach and involves case studies in various fields that face significant development pressures, such as industry, mining, and tourism. The study results show that although local governments can set Regional Spatial Plans (RSP), political factors, weak oversight, and investment interests often override environmental aspects. Local government policies are efforts to unite development interests with ecological conservation. This article concludes that the effectiveness of regional spatial management policies in the regions is highly dependent on institutions' ability, management quality, community involvement, and political courage in balancing the interests of development and preservation. Improved rules, the incorporation of spatial information systems, and enhanced cooperation between parties are essential to achieve fair, sustainable, and change-sensitive spatial planning at the local level. This research suggests strengthening the capabilities of regional institutions, unifying appropriate spatial data, and community participation in the spatial planning and monitoring process.